Public Garden of São Manuel: a comparative study of the arboreal species from the project by Reynaldo Dierberger (1928) and nowadays (2022 - Silva, Adélia Guiomar da; Angélico, Talita dos Santos; Seawright, Andréa Móra Gonçalves; Enokibara, Marta (Revista Nacional de Gerenciamento de Cidades, 2022)
The Public Garden of São Manuel was remodeled in 1928 by the Paulista landscaper Reynaldo Dierberger (1899-1977) and executed by the firm Dierberger & Cia, founded in 1893 in the city of São Paulo by the family' patriarch, João Dierberger. This firm was, until the 1940s, one of the most important ones in the production and commercialization of plants, projects, and execution of gardens. The project elaborated for São Manuel has particular importance for being one of the rare gardens executed by the firm Dierberger, still preserved in its structural aspects. The garden is also a testimony of São Manuel's history since its birth. Furthermore, there is a blueprint of the original project, with handwritten notes by the author about the plant species to be used in this garden. So far, this is the only author's project found in São Paulo´s state, among hundreds of projects, where there is a specification of the vegetation. In this context, the present study aimed to identify and locate the remaining trees and palms of the 1928 project that still exist today. The research used the remodeling project´s blueprint, historical iconography, dissertations, articles, and the georeferenced botanical survey (February 2022). The results show that most of the trees and palm are no longer present or have been replaced by other species and that the upper part of the garden is the one that still preserves part of the vegetal composition.